The Relationship between Mindset and Grit in students at Nusa Cendana University - Bolla, Julya Roviyanti Putri; Junias, Marylin Susanti; Keraf, M. K. P. Abdi; Kiling, Indra Yohanes (Journal of Health and Behavioral Science, 2024)
The lecture process experienced by students often makes them vulnerable to experiencing stressful conditions and even loss of motivation in undergoing lectures. How students overcome problems, difficulties, and challenges in study is related to their grit. Grit is a long-term passion and perseverance that helps individuals to stick to their commitments. This research aims to determine the relationship between mindset and grit in students at Nusa Cendana University. The method in this research is correlational quantitative. The subjects of this research were 268 active students at Nusa Cendana University who were at least in the third year of college. Spearman’s Rho correlation test results showed that mindset was positively related to grit (r = 0,372). Higher mindset is associated with higher grit.